2021
DOI: 10.33394/jk.v7i4.3881
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Indonesian Students on the Role of Teachers in Offline and Online Learning During the Covid-19 Pandemic Period

Abstract: This study aimed to analyze student perceptions regarding the role of teachers in classroom learning compared to online learning during the Covid-19 pandemic by applying a quantitative approach with a survey method. Population in this study was students throughout Indonesia who were actively learning during the Covid-19 pandemic.  The research used Cluster Sampling technique by distributing online forms to students studying at home in all provinces in Indonesia, from Aceh to Papua; while sampling was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…This means that the implementation of limited face-to-face learning does not only pay attention to how schools can facilitate the facilities and infrastructure needed in limited face-to-face learning but also must pay attention to the quality of children's rights in learning. Moreover, most students in Indonesia still prefer face-to-face learning in class (Alhamuddin & Sebua, 2021) Thus, adequate resources both in quantity and quality need to be considered in the implementation of limited face-to-face learning. In addition, the commitment and attitude of resources are also important in the implementation of limited face-to-face learning.…”
Section: ) Human Resourcesmentioning
confidence: 99%
“…This means that the implementation of limited face-to-face learning does not only pay attention to how schools can facilitate the facilities and infrastructure needed in limited face-to-face learning but also must pay attention to the quality of children's rights in learning. Moreover, most students in Indonesia still prefer face-to-face learning in class (Alhamuddin & Sebua, 2021) Thus, adequate resources both in quantity and quality need to be considered in the implementation of limited face-to-face learning. In addition, the commitment and attitude of resources are also important in the implementation of limited face-to-face learning.…”
Section: ) Human Resourcesmentioning
confidence: 99%
“…Many researchers have researched teachers' perceptions of online teaching and learning at various school levels. Such as (Alhamuddin & Zebua 2021), their study used a survey method conducted in all provinces in Indonesia from Aceh to Papua. Their study showed that most students in Indonesia still preferred face-to-face learning in class.…”
Section: Abidahmentioning
confidence: 99%
“…Since most of the previous scholars only investigated at the high school level, the researcher had in mind to seek the perceptions of teachers and students toward the switch from offline to online learning at the primary school level. Many other scholars reported the perception of online learning, such as university students (Yusny, 2021), Senior high school (Nashir & Laili, 2021), and Indonesian students (Alhamuddin & Zebua, 2021). Even though their studies showed that offline learning was preferable to online learning, those were conducted in high school.…”
Section: Introductionmentioning
confidence: 99%
“…This is because The role of the teacher directly cannot be replaced by technology, and moral or affective values in these domains cannot be carried out optimally by teachers during online learning. (Alhamuddin & Zebua, 2021) Education is one of the most important factors contributing to social and economic development. Quality education is essential to ensure that individuals are equipped with the skills and knowledge necessary to succeed in life.…”
Section: Introductionmentioning
confidence: 99%